Study of Hydrolysis Process from Pineapple Leaf Fibers using Sulfuric Acid, Nitric Acid, and Bentonite Catalysts - Bayu Wiyantoko; Rika Rusitasari; Rahma Novia Putri (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The hydrolysis process of pineapple leaf fibers has been carried out using sulfuric acid, nitric acid, bentonite catalyst, and activated bentonite catalyst. The sugar content of the hydrolysis product was identified using the phenol-sulfuric acid method by UV-Visible spectrophotometry. The disposal of pineapple leaf is a big problem even though it has high cellulose content (70–80%) and very promising to produce sugar by hydrolysis process. The purpose of this experiment was to determine the effectiveness of homogeneous and heterogeneous catalysts related to sugar levels in pineapple leaf fiber. The variables in this study were the sampling time during the hydrolysis process at a temperature of 100 °C and the addition of homogeneous and heterogeneous catalysts. The homogeneous catalysts were sulfuric acid and the nitric acid meanwhile heterogeneous catalyst was thermally activated bentonite and acid-activated bentonite. The results obtained highest sugar content reached at 150 minutes using chemical activated bentonite catalysts at 6.459 g/L and the addition of catalysts affected sugar yields, speed up the reaction, bentonite as a good catalyst, and gave good prospect for ethanol production in further process. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).